Elina Screen: Sylloge of Coins of the British Isles, vols. 65 & 66: Nor- wegian Collections, Part I: Anglo-Saxon Coins to 1016 & Part II: Anglo-Saxon and later British Coins 1016-1279. - Moesgaard, Jens Christian (Collegium Medievale, 2016)
These two substantial volumes publish an impressive 4230 coins struck at the British Isles prior to 1279 and kept in Norwegian Museums. They are volumes 65 and 66 in the Sylloge of Coins of the British Isles (SCBI). Since the publication of volume 1 in 1958 (Fitzwilliam Museum, Cambridge) this series has under the auspices of the British Academy made thousands of coins kept in public or private collections easily available and thus largely stimulated research into British coins.